2016
DOI: 10.1007/s12018-016-9225-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatasia: Review of Bone Mineral Metabolism, Pathophysiology, Clinical Presentation, Diagnosis, and Treatment

Abstract: Hypophosphatasia (HPP) is a rare, inherited form of rickets or osteomalacia due to reduced activity of tissue non-specific alkaline phosphatase (TNSALP) caused by a loss of function mutation in the TNSALP gene marked by a low serum alkaline phosphatase. The ratio of PPi to Pi is crucial in the mineralization process. This process is regulated by the interaction of three phosphatases present in matrix vesicles: the mineralization promotors TNSALP and phosphatase orphan 1 (PHOSPHO1) and the mineralization inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 116 publications
0
2
0
1
Order By: Relevance
“…A common manifestation of loss of TNAP activity or mutations to ALPL gene causes a systemic bone disease called hypophosphatasia (HPP) resulting in hypomineralization of hard skeletal tissues including bone and teeth [ 106 , 107 ]. Several missense mutations are reported in human ALPL gene corresponding to aminoacid changes in the protein [ 106 , 107 , 108 ]. At the time of writing this review, 409 mutations in TNAP have been reported owing to its clinical heterogeneity.…”
Section: Tnapmentioning
confidence: 99%
See 1 more Smart Citation
“…A common manifestation of loss of TNAP activity or mutations to ALPL gene causes a systemic bone disease called hypophosphatasia (HPP) resulting in hypomineralization of hard skeletal tissues including bone and teeth [ 106 , 107 ]. Several missense mutations are reported in human ALPL gene corresponding to aminoacid changes in the protein [ 106 , 107 , 108 ]. At the time of writing this review, 409 mutations in TNAP have been reported owing to its clinical heterogeneity.…”
Section: Tnapmentioning
confidence: 99%
“…Milder forms of the disease include deformities of extremities, early deciduous teeth loss and other dental manifestations. In severe cases of HPP, prenatal death of foetuses is seen due to complete absence of minerals in their skeleton [ 106 , 107 , 108 ]. Epileptic seizures, craniosynostosis, respiratory failure and death are also associated in extreme forms of HPP.…”
Section: Tnapmentioning
confidence: 99%
“…O recobrimento de superfícies utilizando HA foi introduzido em meados dos anos 80 para promover a fixação entre o osso e o implante e tem sido bem sucedido devido ao seu favorável comportamento in vivo 84 . Porém, suas propriedades mecânicas fracas, como baixa resistência a flexão e tenacidade, continuam sendo um obstáculo.…”
Section: Recobrimentos De Haunclassified